A novel candle light-style OLED with a record low colour temperature. Issue 89 (9th October 2019) - Korshunov, Vladislav M.; Chmovzh, Timofey N.; Knyazeva, Ekaterina A.; Taydakov, Ilya V.; Mikhalchenko, Ludmila V.; Varaksina, Evgenia A.; Saifutyarov, Rasim S.; Avetissov, Igor C.; Rakitin, Oleg A.
Abstract : Candle light-style OLEDs based on new D–A–π–A type molecules incorporated into Alq3 matrix were developed. A record low color temperature of 1722 K OLED radiation was achieved, which is by 80 K lower than that of the best devices reported previously. Abstract : The possibility of using a single light-emitting layer consisting of newly synthesized fluorescent small organic molecules of D–A–π–A type incorporated into a conductive matrix together with an electron conductive Alq3 layer in order to form radiation in candle light-style OLEDs was shown for the first time. A record low color temperature of 1722 K OLED radiation was achieved, which is by 80 K lower than that of the best devices reported previously.